Scentless Plant Bugs, Jadera sp. (Insecta: Hemiptera: Rhopalidae) - Frank W. Mead; Thomas R. Fasulo (EDIS)
This document is EENY-130 (originally published as DPI Entomology Circular 277), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: May 2000.